Epidemiology of myopia and the effect of orthokeratology on controlling the disease - Adrianna Gorecka; Agnieszka Kaczyńska; Dagmara Gorecka; Karol Chromiak; Katarzyna Urbańska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2022)
Introduction and objective Myopia is a defect of vision, which makes it impossible to see remote objects clearly. The disease can also lead to serious ocular problems. Myopia affects about 30% of the world population and -according to the estimates- that percentage is about to increase up to 50% within the next 30 years. Orthokeratology is a relatively new method on non-surgical, reversible correction of myopia. Specially designed lenses, worn at night, affects the shape of the cornea, which results in proper vision during the day. Review methods The aim of the study was evaluation of effectiveness of wearing orthokeratology contact lenses based on a review of medical literature published on PubMed in the last 5 years. Abbreviated description of the state of knowledge Research results show that wearing orthokeratology lenses have beneficial effects. Reduction of axial length of the eyeball and curvature of the cornea were observed. Progression of myopia was five times slower in children study group and three times slower in adult study group compared to control groups. It was proved, that favourable health effects persist through the first eight years of treatment. Due to the fact, that cornea has a limited susceptibility, a decrease in efficiency occurs in the following years. Usually no undesirable side effects are reported, yet the possible side effects are mild and disappear after a short time. Summary According to the results of recent studies, we can assume that orthokeratology is a safe and effective method of inhibition of myopia progression. The method may be especially recommended to children, to people working in such conditions, that make wearing standard contact lenses impossible and to people not qualified for laser or surgical vision correction.